An intelligence coordination system toward creating the super-intelligent law firm - Kaomea, Peter (Frontiers in Artificial Intelligence, 2023)
A large law firm typically exhibits a collective intelligence comprised of hundreds or thousands of legal minds aimed at simultaneously engaging thousands of active matters across scores of industries and dozens of practice specialties with distinct doctrinal and procedural characteristics. The firm is challenged not only to achieve successful, cost-effective outcomes for its clients, but must also simultaneously, in competition with other firms and alternative service providers, attract and cultivate talent, develop and coordinate capabilities across multiple evolving areas of practice and continually improve a robust collective intelligence to gain a competitive edge. As various types of machine intelligences and tools are introduced, firms must also groom these into the collective. In this paper we explore a human-machine hybrid system for addressing this large scale, multi-dimensional, dynamic optimization challenge to coordinate a collective intelligence of humans and machines. Machine intelligence is needed to handle the computational complexity and it is complemented by human intelligence to help handle exceptions and novel situations. We believe this approach has potential for transforming the collective intelligence that is the large law firm.